Pendugaan Cadangan Karbon Above Ground Biomass (AGB) pada Tegakan Hutan Alam di Kabupaten Langkat (The Estimate of Carbon Stocks Above Ground Biomass (AGB) of Natural Forest Stands in Langkat District) - Maurin Lis Evan Panggabean; Rahmawaty Rahmawaty; Riswan Riswan (Program studi Kehutanan USU, 2013)
Climate change is a direct impact of global warming. An effort to reduce the rate of global warming is to estimate the potential of carbon stored. To find out how potential carbon stored, the estimate approaches of the count can use remote sensing data and measurements in the field (ground check). The study aimed to calculate carbon stocks above ground biomass in natural forest stands in Langkat and mapped the distribution of carbon by using NDVI method. Non destructive method and landscape scale Normalized Difference Vegetation Index (NDVI) method were used in this study. The result showed that the amount of carbon content in above ground biomass in natural forest stands in Bukit Lawang Resort, Tangkahan Resort and Pamah Simelir classified as good, respectively by 213,72 ton/ha, 214,47 ton/ha and 205,99 ton/ha. From the regression equation y = 168,79 + 69,50 * NDVI obtained R2 value of 53% which showed good correlation between the value in the field of carbon calculations with NDVI values. Key words: carbon stock estimate, Above Ground Biomass, natural forest stand.